2021
DOI: 10.24996/ijs.2021.62.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Using Non-dominated Sorting Particle Swarm Optimization Algorithm II for Bi-objective Flow Shop Scheduling Problems

Abstract: A hybrid particulate swarm optimization (hybrid) combination of an optimization algorithm of the particle swarm and a variable neighborhood search algorithm is proposed for the multi-objective permutation flow shop scheduling problem (PFSP) with the smallest cumulative completion time and the smallest total flow time. Algorithm for hybrid particulate swarm optimization (HPSO) is applied to maintain a fair combination of centralized search with decentralized search. The Nawaz-Enscore-Ham )NEH) heuristic algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Dominance Rules (DRs) are used efficiently in reducing the current sequences [23][24][25]. DR is used usually to indicate whether a certain node in a BAB method can be eliminated before calculating its lower bound.…”
Section: Dominance Rules For Single Machine Scheduling Problemmentioning
confidence: 99%
“…Dominance Rules (DRs) are used efficiently in reducing the current sequences [23][24][25]. DR is used usually to indicate whether a certain node in a BAB method can be eliminated before calculating its lower bound.…”
Section: Dominance Rules For Single Machine Scheduling Problemmentioning
confidence: 99%
“…propose the (PSO) and the (GA) as heuristic methods to find approximation solutions for ∑ ∑ and they found that these local search algorithms solve the problem for jobs with reasonable time. The (PSO) algorithm were applied by Hanan [5]. For solving the problem ∑…”
Section: Alaa Sabah Hameedmentioning
confidence: 99%
“…The performance of the (BAB) procedure is compared on 5 problem instances, the sizes of these examples are n = [5,18]. The problem instances were generated randomly, and for each job where , the processing time was uniformly generated in [1,10].…”
Section: The Problems Instancesmentioning
confidence: 99%
“…PSO appoints a set of particles that explore the solutions by moving locally and globally in the search landscape to identify the optimal solution. The movement strategy of the employed particles is inspired by the movement mechanism of a bird swarm, where each particle saves its coordinate path in the search space and correlates with the best captured local and global solution (i.e., local and global optima) to the swarm [3,23,24]. To identify the best solution, the movement of each particle will direct toward the obtained local solution as well as the global solution.…”
Section: Introductionmentioning
confidence: 99%